2005
DOI: 10.1007/s00268-005-7795-z
|View full text |Cite
|
Sign up to set email alerts
|

Histological Grading in Gastric Cancer by Ming Classification: Correlation with Histopathological Subtypes, Metastasis, and Prognosis

Abstract: The aim of this prospective study was to analyze Ming's classification in correlation with other currently used classification systems of gastric cancer. In addition, we wanted to define the prognostic significance of the Ming classification system. The present study analyzed material of 117 patients with gastric carcinoma who underwent D2-gastrectomy with curative intent. All specimens were categorized according to International Union Against Cancer (UICC) classification, World Health Organization (WHO) class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
2
24
0
2
Order By: Relevance
“…None of the studies have reported the degree of FDG uptake according to the Ming classification. As a rationale for low FDG uptake of the diffuse and infiltrative type, it has been postulated that the high number of signet ring cells in the tumors with diffuse type and infiltrative type lead to a reduced FDG concentration in the tumor [4,33]. Another reason could be the lack of expression of the glucose transporter Glut-1 on the cell membrane of most diffuse types of gastric carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…None of the studies have reported the degree of FDG uptake according to the Ming classification. As a rationale for low FDG uptake of the diffuse and infiltrative type, it has been postulated that the high number of signet ring cells in the tumors with diffuse type and infiltrative type lead to a reduced FDG concentration in the tumor [4,33]. Another reason could be the lack of expression of the glucose transporter Glut-1 on the cell membrane of most diffuse types of gastric carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate tissue samples were acquired by endoscopic biopsy or surgical resection. Microscopically, the tubular, papillary, mucinous and poorly cohesive types were classified according to the WHO classification, the intestinal type and diffuse type were classified according to the Lauren classification, and the infiltrative type and expanding type were classified according to the Ming classification, as described previously [4,5,25,26]. In the tubular type of adenocarcinoma, the tumors were classified into well, moderately and poorly differentiated types according to the histological differentiation.…”
Section: Histopathologic Classificationmentioning
confidence: 99%
See 3 more Smart Citations